Pengembangan Skala Regulasi Diri dalam Pembelajaran Daring (Self-Regulated Online Learning Scale) pada Mahasiswa - Nurul Arbiyah; F.A. Triatmoko (Fakultas Psikologi Universitas Pancasila, 2016)
One thing that distinguishes learn using network (online) and face to face learning is the separation between teachers and students that facilitated using online technology media, such as the Internet. Each participant in online learning should be able to manage their own learning (self-regulated leaner) in order to follow the lesson well. Development of a valid and reliable Self-Regulated Online Learning (SROL) scale is needed to help us address issues regarding the success of online learning, especially in developing various research on self-regulated online learning and its relation with other variables. The development of this measure carried out on 30 students' online classes by Universitas Indonesia. Single-trial test with Cronbach alpha generate the score which means SROL scale has high internal consistency. Calculation of the validity with criterion validity, which indicates that the measuring instrument SROL valid to predict students' academic achievement. Based on the integrative analysis of items, we selected 24 best items that distinguish individuals who higher and lower self-regulated online learning. Norms based on the group by using Scaled Score, with a mean of 10 and standard deviation of 3.